Persepsi Mahasiswa terhadap Penggunaan Google Translate dalam Mata Kuliah Penerjemahan untuk Wisata dan Acara - Maulidiyah, Fitrotul (Jurnal Penerjemahan, 2023)
This study aims to identify the perceptions of students of D4 in English for the Tourism Industry Study Program at the State Polytechnic of Malang on the use of Google Translate (GT). Twenty-one students were selected as the research participants. The instruments used were questionnaires and interviews. The questionnaires and interviews were about the students’ perceptions regarding the students’ frequency of using GT, students’ agreement or disagreement regarding the use of GT, as well as the advantages and disadvantages of using GT. The qualitative-descriptive analysis found that most respondents indicated a relatively high dependency on the use of GT in completing their translation assignments. The results revealed that all participants sometimes used GT and felt confident. Even though using GT provided several disadvantages, some students still believe GT offered more advantages than disadvantages. However, most students stated that they edited the translation results from GT before submitting them. Keywords: Google Translate, machine translation, translation.